Participatory Branding Mentoring for Home-Based MSMEs in Wanakaya Village - Jajat Sudrajat; Daniel Ady Putra; Nyimas Riri Badriah (SOCIRCLE : Journal Of Social Community Services, 2024)
Home-based micro, small, and medium enterprises (MSMEs) often depend on personal networks while lacking a clear visual identity and visible business information at their production locations. This community service program aimed to strengthen the basic branding readiness of two food MSMEs in Wanakaya Village, Cirebon Regency, through participatory diagnosis, brand-identity planning, packaging prototyping, printed-banner development, and output handover. The program was implemented from 4 to 25 February 2023 with Milik Catering and Dapur Mamah Aldi as the intensive partners. Evidence was obtained from field observations, owner consultations, facilitator notes, design files, completion checklists, and activity photographs documented in the official KKN report. The initial assessment found that both businesses lacked printed signs, while Milik Catering also lacked a consistent logo and packaging application. The mentoring process involved clarifying the business name, product characteristics, desired impression, visual symbols, color direction, essential ordering information, and placement needs before the designs were developed in CorelDRAW and reviewed with the owners. The verified outputs comprised one logo, one packaging prototype, and two printed business banners, representing complete delivery of the four planned branding outputs. The program demonstrates that a short, owner-involved branding process can convert general branding advice into tangible and reusable visual assets. However, customer recognition, enquiries, sales, and sustained use were not measured; therefore, the results are limited to documented processes, completed outputs, and initial owner-level readiness.